Pluralisme Agama, Ulama Sufi, dan Pertarungan Wacana: Religious Pluralism, Sufi Scholars, and the Discourse Struggle - Hafidz Hasyim (Fenomena, 2012)
The Sufi perspective provides a clear lens to examine the discourse of religious pluralism. Sufi religious views encompass two aspects: the exoteric and the esoteric. The exoteric aspect of religion is the outward dimension, emphasizing sharia, forms, and religious symbols. Meanwhile, the esoteric aspect is the innermost dimension of every religion, focusing on inner, spiritual experiences to attain the ultimate reality, God. Sufi scholars in Jember emphasize inner experiences, as the purpose of religion is to reach God through such experiences, without neglecting sharia, which serves as the path to this goal. However, these Sufi scholars avoid debating sharia, as it pertains to methodology. Their rationale is that, fundamentally, all religions—regardless of form or type—aim to face the Divine. The error and deviation, according to Sufi scholars, lie in directing religion toward anything other than Allah. Perspektif Sufi mampu melihat secara jelas wacana pluralisme agama. Perspektif agama Sufi memandang dua aspek, yaitu aspek eksoterik dan esoterik. Aspek eksoterik agama adalah aspek lahiriah yang menekankan pada syariah, bentuk, dan simbol-simbol agama. Sementara aspek esoterik adalah aspek terdalam dalam setiap agama, yang menekankan pengalaman batin dan spiritual dalam mencapai realitas sejati, yaitu Tuhan. Ulama Sufi di Jember memberikan perhatian pada pengalaman batin, karena tujuan agama adalah mencapai Tuhan melalui pengalaman batin, namun tidak mengesampingkan syariah, sebab syariah adalah jalan untuk mencapai tujuan tersebut. Namun, ulama Sufi Jember tidak memperdebatkan wilayah syariah karena hal itu berkaitan dengan metode. Alasan pandangan ulama Sufi ini adalah bahwa pada dasarnya semua agama, terlepas dari bentuk dan jenisnya, bertujuan untuk menghadap Yang Ilahi. Kesalahan dan penyimpangan menurut ulama Sufi adalah ketika agama tidak ditujukan untuk selain Allah.